Effects of Lead Acetate on Light Protein of Drosophila melanoigaster - Haq, Rizwanul; Khan, M. Farhanullah; Haq, Ehteshamul (Journal of Basic & Applied Sciences, 2012)
Lead is supposed to be an important poisonous waste, which could contaminate the environment, therefore, insects could be influenced easily by the lead. Drosophila melanogaster, was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations of 0.125 mg, 0.25 mg, 0.5 mg, 1.0 mg and 2.0 mg. It was observed that, under the effects of lead abnormalities, and deformity were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards due to lead contamination, which exerts a specific physiological and morphological effect on these flies.